Waters of unity: maritime history of Nusantara from Hindu-Buddhist kingdoms to the pre-colonial era - Ismail Ali,; Mohd Firdaus Abdullah, (Penerbit Universiti Kebangsaan Malaysia, 2024)
The seas and oceans have long served as sources of inspiration and knowledge, challenging human perceptions historically rooted in myths and superstitions. Beyond their symbolic significance, these maritime spaces functioned as critical conduits for interregional connections, fostering mutual understanding, unity, and economic prosperity. In this study, we examine the maritime history of Nusantara, focusing on the Hindu-Buddhist kingdoms and the subsequent pre-colonial era, to explore the dynamic interplay between indigenous maritime traditions and external seafaring influences. Employing a qualitative approach grounded in the Annales School framework, this research synthesises secondary data from historical, archaeological, and anthropological sources to uncover the patterns of continuity and change in maritime governance. By highlighting the underexplored role of Nusantara in shaping regional civilisations and navigating external pressures, this study bridges historical narratives with contemporary discussions on maritime governance. Our findings offer lessons from the past to inform sustainable development, regional cooperation, and strategic management of oceanic resources in the Indo-Pacific region. By focusing on the intersections of local maritime agency and global forces, we aim to advance the understanding of how maritime histories continue to influence the present and future.